Impacts of temperature variation on performance, life-history and flight ability of the false codling moth, Thaumatotibia leucotreta (Lepidoptera: Tortricidae) - Boersma, Nevill (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScConsEcol)--Stellenbosch University, 2018.